Formation mechanism and prediction model of juvenile delinquency - Xu, Shuhui; Yu, Junwen; Hu, Yu (Frontiers in Psychology, 2023)
Exploring the formation mechanism of juvenile delinquency is of great significance to prevent juvenile delinquency. The present study examined relations and interactions among juvenile delinquents' self-consciousness, family factors, social relationships, belief in a just world, and legal consciousness, and then developed a predictive model to distinguish between juvenile delinquents and non-delinquents. The results showed that family factors have a significant influence on the formation of juvenile delinquents' self-consciousness and there are notable differences in family environment and self-consciousness between delinquent and non-delinquent adolescents. Due to the complex interactions among juvenile delinquency's self-consciousness, family factors, social relationships, belief in a just world and legal consciousness, adolescents' self- consciousness and social relationships can be utilized to predict and classify the groups of delinquent and non-delinquent adolescents effectively. Therefore, the key to preventing juvenile delinquency is to improve their self-consciousness and develop their prosocial relationships.